2020
DOI: 10.21511/bbs.15(3).2020.07
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between banking sector development and inclusive growth

Abstract: According to an inclusive growth framework, the top objectives of the economic policy shift from increasing incomes themselves to well-being. While banking sector development has conventionally been considered a growth factor, there is no clear understanding of its impact on inclusive growth. This article explores how the banking sector’s qualitative development, measured in dimensions of the services availability, lending supply, stability, and reliability of banking activity, relates to inclusive growth. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This situation tells us that both the banking sector performance of OECD countries is important for economic development and economic development is important for the banking sector performance. This result of the study is similar to the findings obtained Altunç (2008) study for Turkey in 1970-2006and Pradhan et al (2014a for ASEAN countries over the period of 1961-2012. However, it does not match the study findings of Akpansung and Babalola (2011), Awdeh (2012), Ofori-Abebrese et al (2017, Mhadhbi et al (2020) and Samour et al (2022), which found a one-way causality relationship from economic development to bank credit.…”
Section: Westerlund Cointegration (2007)supporting
confidence: 91%
See 1 more Smart Citation
“…This situation tells us that both the banking sector performance of OECD countries is important for economic development and economic development is important for the banking sector performance. This result of the study is similar to the findings obtained Altunç (2008) study for Turkey in 1970-2006and Pradhan et al (2014a for ASEAN countries over the period of 1961-2012. However, it does not match the study findings of Akpansung and Babalola (2011), Awdeh (2012), Ofori-Abebrese et al (2017, Mhadhbi et al (2020) and Samour et al (2022), which found a one-way causality relationship from economic development to bank credit.…”
Section: Westerlund Cointegration (2007)supporting
confidence: 91%
“…At the same time, according to many researchers, the economic development of developing and developed countries is found to be increasing by financial globalization (Bhanumurthy and Kumawat, 2020;Egbetunde & Akinlo, 2015;Sahoo and Sethi, 2020;Schularick and Steger, 2010). Liang and Reichert (2006) focuse on the period 1960-2000 and use the multiregression model to determine the result that banking sector development and investment increased the economic development of developed and developing countries. Pradhan et al (2014a) analyzes the relationship between economic growth, banking sector development, stock market development and other macroeconomic variables in ASEAN countries.…”
Section: Literature Reviewsmentioning
confidence: 99%